Lab management. The laboratory staffing crunch. - Stegall T; Stegall MS (Medical Laboratory Observer (MLO), 2006)
Educational initiatives, HR-positioning strategies, Lean/Six Sigma approaches, and equipment/automation solutions may help ease lab staffing problems.